Value of C⁃reactive protein/albumin ratio，pancreatic stone protein combined with interleukin⁃12 on prediction of offline extubation outcomes of patients with mechanical ventilation in severe pneumonia - HOU Hongmei，PENG Feng，XIAO Yun (Zhongguo linchuang yanjiu)
Objective To explore the predictive value of the ratio of C ⁃ reactive protein to albumin（CRP/ALB），pancreatic stone protein（PSP），and interleukin⁃12（IL⁃12）for the outcome of offline extubation in patients withmechanical ventilation in severe pneumonia，in order to guide clinical decision⁃making and enhance weaning success rates. Methods Ninety patients with severe pneumonia admitted to Yuebei People's Hospital from January 2021 to December 2023 were selected as the study subjects. According to the outcome of offline extubation，they were divided into failure group（n=26）and success group（n=64）. The general information，serum CRP/ALB，PSP，IL⁃12 levels on the day of admission and before spontaneous breathing trial（SBT）were compared between the two groups. Pearson correlation coefficients were used to analyze the association of serum indicators with clinical pulmonary infection score（CPIS）and acute physiology and chronic health evaluation Ⅱ（APACHE Ⅱ）scores. Logistic regression equation was used to analyze the impact of serum CRP/ALB，PSP，and IL⁃12 on the outcome of offline extubation from mechanical ventilation in severe pneumonia. Receiver operating characteristic（ROC）curves and area under the curve（AUC）were used to analyze the predictive efficacy of serum indicators. Results （1）Compared with the success group，the CPIS，APACHE Ⅱ score and serum CRP/ALB，PSP，IL⁃12 levels on the day of admission and before SBT in the failure group were higher（P<0.01）.（2）Serum CRP/ALB，PSP，IL⁃12，CPIS and APACHEⅡscores before SBT were selected for follow⁃up study according to the recency effect. In patients with severe pneumonia who failed of offline extubation from mechanical ventilation，CPIS and APACHEⅡscores before SBT were positively correlated with serum CRP/ALB，PSP，and IL⁃12 levels，respectively（P<0.05）.（3）After adjusting，CRP/ALB，PSP，and IL⁃12 before SBT were still associated with failure of offline extubation from mechanical ventilation in patients with severe pneumonia（P<0.05）.（4）The predictive efficacy of CRP/ALB+ PSP+IL⁃12 before SBT［AUC（95%CI）：0.936（0.864-0.977）］for failure of offline extubation from mechanical ventilation in patients with severe pneumonia was significantly better than that of individual predictive efficacy of CRP/ALB，PSP and IL⁃12［0.822（0.727-0.895），0.749（0.647-0.835），0.827（0.733-0.899）］. Conclusion Serum CRP/ALB，PSP，and IL⁃12 are closely related to the failure of offline extubation in patients with severe pneumonia. The combined detection of these three markers has good predictive efficacy and is helpful inguiding clinical diagnosis and treatment.